Analisa Unjuk Kerja Mobile Based Tranceiver Station untuk Kestabilan Infrastruktur Sistem Komunikasi Seluler - Melvi .; Ardian Ulvan; Ricky Fernando (Jurnal Rekayasa Elektrika, 2014)
The stability of the telecommunications system infrastructure, particularly in the area experienced disastrous, should be restored as soon as possible to recover communication services. One solution for the recovery is by implementing a mobile Base Transceiver Station (BTS), which can be installed easily. In this work, an analysis of Arrow type Combat mobile BTS is conducted in the area of Terbanggi Agung, Central Lampung. The performance measurement and data analysis are performed on the three sectors of the cell coverage. The Received Total Wideband Power (RTWP), Call Completion Success Rate-Packet Switched (CCSR-PS) and Call Completion Success RateCircuit Switched (CCSR-CS) are taken at regular intervals (per hour for 24 hours), based on the standard Key Performance Indicator (KPI) of the International Telecommunication Union (ITU). The results showed that the average value of RTWP on each sector is 105 dB, while the value of CCSR-PS and CCSR-CS are above 95%. Moreover, the measured value of RTWP are less than the standard, which is assumed due to interference from neighbour BTS uplink frequency, despite the possibility of interference was small. In overall, the RTWP values, the CCSR-PS and CCSR-CS meet the standards of the ITU-T Recommendation E.850.Keywords: mobile BTS, received total wideband power (RTWP), call completion success rate- packet switched (CCSRPS), call completion success rate-circuit switched (CCSR-CS)